MARITIME DIPLOMACY AND THE FIGHT AGAINST IUU FISHING IN THE NORTH NATUNA SEA: INDONESIA UNDER JOKO WIDODO (2014–2019) - Novansyah, Giffariel; Dwiastuti, Ilmi (Universitas Padjadjaran, 2025)
The North Natuna Sea, officially designated by the Indonesian government in 2017, has become a hotspot for Illegal, Unreported, and Unregulated (IUU) fishing. President Joko Widodo’s “Global Maritime Fulcrum” doctrine emphasizes the use of maritime diplomacy to address various sources of conflict in Indonesia’s maritime domain, with IUU fishing explicitly identified as one of these challenges. This study seeks to answer the research question: How has maritime diplomacy been implemented to address IUU fishing in the North Natuna Sea during President Joko Widodo’s first term (2014–2019)? This thesis then seeks to learn the implementation of maritime diplomacy to address the issue of IUU fishing within President Joko Widodo’s first term (2014-2019) while this period also remarks the high number of boat sunken under Pudijiastutui’s policy. The study employs a qualitative research method, drawing on government policy documents, official statements, media reports, and secondary academic literature. Christian Le Mière’s concept of Maritime Diplomacy serves as the main analytical framework. The findings suggest that Indonesia’s maritime diplomacy in this period can be categorized into three main actors: the military (Tentara Nasional Indonesia), constabulary forces (the Indonesian Water Police and the Ministry of Fisheries’ Pengawas Perikanan), and civilians (local Indonesian fishers). Each actor contributes to different forms of maritime diplomacy in the North Natuna Sea. First, coercive maritime diplomacy—implemented by the military and constabulary forces—proved effective in deterring foreign illegal fishing vessels through arrests and the sinking of ships following legal proceedings. Second, persuasive or cooperative maritime diplomacy—conducted by all three actors through patrols, joint operations, and training—had a more limited impact, as it did not significantly reduce the recurrence of IUU fishing activities. Thus, this study highlights both the strengths and limitations of Indonesia’s maritime diplomacy, showing that coercive measures are more immediately impactful, while cooperative measures face challenges in sustaining long-term effectiveness.